Prosthodontic Rehabilitation for Edentulous Ridges: Clinical Cases at a Glance - Singh, Sandeep; Rathee, Manu; Singla, Shefali; Chahal, Sujata; Divakar, S; Singh, Sarthak; Mittal, Surbhi; Diwan, Kritika; Balavignesh S (Prosthodontic Rehabilitation for Edentulous Ridges: Clinical Cases at a Glance, Edition 1, 2024)
The book "Prosthodontics Rehabilitation for Edentulous Ridges - Clinical Cases at a Glance" presents a comprehensive resource tailored for postgraduate dental students. With a focus on precision and clarity, the book offers detailed descriptions supported by illustrations, serving as a practical manual for students navigating complex cases. Addressing a noted gap in existing literature, the book integrates removable, fixed, implantology, and digital cases, providing a holistic approach to prosthodontic rehabilitation. Designed to be an invaluable resource for dental schools, this book equips students with the knowledge and skills necessary to confidently address a wide range of specialized cases in their future practice.